(3fJjLI GdJMbjb aj HYV Cgd GdTQa GdhKjbs - (3eMeO Hf CMeO Hf GdeSfGhj Hf eMeO Hf CHj HcQ, CHh YHO Gddg GdOdGFj,J (B1136 (3g` s
(3ChdgG (B:s
(3hHYO , agPg dbWI YLdGf NOeJ HgG LfGH TjN GdeTGjN GdWGdY ef LjdGf hjTJed Ydi HYV eGjJYdb Hg Ke eG jJYdb HHYV YbHg s
(3BNQgG (B:s
(3hai GdMOjK GMJeGdGJ CNQi de fPcQgG gfG GfJgi JJeg fPcQ ajgG HbjI TLQI GdCfSGH ai eSGFd ef gPG GdcJGH hYehe efaYJgG Ef TGA Gddg hgPg UhQJgG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B34 - (3U(B127s
(3JTJed Ydi LOGhd HTLQI GdfeSHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B13 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B259s
(3Odjd eDQN GdeZQH (B- (3U (B132 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B442 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(310 (3O(B) s
Keywords: (3GdJGQjNs